The Weighted Average Cost of Capital and Shareholder Wealth Maximization - Beranek, William (Journal of Financial and Quantitative Analysis, 1977)
A set of theorems was derived based on the following set of axioms: (1) financial management seeks to maximize the wealth of existing shareholders; (2) all projects being considered at period 0 are of one period duration and possess the attribute that their adoption or rejection by the firm will not affect the business risk of the firm's asset portfolio; and (3) the ratio of debt to total book capital is given as α, and r and k reflect the firm's business and financial risk however perceived by investors.It was shown that the NPV of any project satisfying the above conditions could be evaluated for accept-reject purposes with a CC involving book weights. This CC yielded an NPV numerically equal to the NPV using market value weights under special circumstances, namely, when k = r (1 − λ) or when M0/V0 = 1 − α, a special case of which is M0 = (1 −α)c0, i.e., if the firm were at its investment margin. After determining the book value CC, which is denoted as β, it was shown that it can be applied repeatedly for testing period 0 projects satisfying our axioms, even if these projects are unknown to management at the outset of the period. A market value CC, denoted as γ, was derived which gives identical accept-reject signals as the procedure.